Audit committee rules in Indonesia: Determinants of compliance and their association with restatements / Ari Kuncara Widagdo - Ari, Kuncara Widagdo (2014)

(untitled)
As a response to the 1997 Asian financial crisis, Indonesia intensively pursued corporate governance reforms. However, the reforms were found to be unsatisfactory; some factors, such as specific business characteristics, were considered as contributing to the ineffectiveness of the reforms. Therefore, Indonesia provides an interesting setting to examine the effectiveness of the implementation of the Anglo-American corporate governance model in an emerging economy context. This study focuses on one Anglo-American corporate governance mechanism that has been actively promoted in Indonesia, namely, the audit committee. The objectives of the study are three-fold: (1) To examine the association between public listed companies with specific business characteristics (namely family control, politically connected independent commissioners, and foreign institutional investors) and their level of compliance with audit committee rules; (2) To examine whether the compliance, which also indicates the level of audit committee effectiveness, is associated with restatements of financial statements, and; (3) To examine the influence of family control on the association between audit committee effectiveness and restatements of financial statements. This study is divided into two interrelated research stages: a study on the determinants of compliance of public listed companies with audit committee rules (Research Stage 1), and a study on the association between audit committee effectiveness and restatements (Research Stage 2). Research Stage 1 employs short balanced panel data that, in total, cover 828 company-year observations for the period 2006-2008. The method of analysis used is feasible generalised least squares (FGLS), as the presence of heteroskedasticity and autocorrelation are noted in the data. Meanwhile, Research Stage 2 utilises cross sectional data, namely, 158 restating companies for the period 2006-2012 matched with 158 control companies for the same period. The method of analysis is matched pair logistic regression. The results of Research Stage 1 indicate that different types of family control have different effects on the level of compliance of public listed companies with audit committee rules. Family-controlled companies with family members on boards are less likely to comply with audit committee rules. In contrast, companies controlled through family shareholding but without family involvement in their daily business activities are more likely to comply with audit committee rules. Additionally, public listed companies with politically connected independent commissioners are less likely to comply with audit committee rules. As expected, public listed companies with large, genuine foreign institutional investors are more likely to comply with audit committee rules. Meanwhile, the results of Research Stage 2 reveal that audit committee effectiveness is not significantly associated with restatements of financial statements. This implies that the presence of an audit committee might be just cosmetic or symbolic. However, the use of restatements of financial statements as a proxy for financial reporting quality might contribute to the insignificance of audit committee effectiveness because this proxy might not be appropriate in the Indonesian environment.